Nutritional status and associated factors among hospitalized adult patients in comprehensive specialized hospitals of Western Ethiopia - Birtukan Kebede Moti; Gudina Egata; Desalegn Wirtu Tesso (PLoS ONE, 2026)
Background Malnutrition is common among hospitalized patients but is often overlooked in low- and middle-income countries like Ethiopia. Therefore, this study aims to determine its prevalence and identify associated factors among adult patients admitted to comprehensive specialized hospitals in Western Ethiopia. Methods A facility-based cross-sectional study was conducted among 1,106 randomly selected adult patients admitted to comprehensive specialized hospitals from December 16, 2023 to April 16, 2024. The sample was proportionally allocated by patient population. Data were collected using Kobo Toolbox, then exported from Microsoft Excel to Stata version 17 for analysis. Nutritional status was assessed at admission using the Subjective Global Assessment (SGA). Ordinal logistic regression was applied after verifying the proportional odds assumption, with the Brant test used for model validation. Adjusted odds ratios (AORs) alongside 95% confidence intervals (CIs) were computed, and statistical significance was set at p < 0.05. Results Among all study participants, 24.5% (95% CI: 21.8%, 27.4%) were severely malnourished, while 34.4% (95% CI: 31.4%, 37.6%) were moderately malnourished. In the multivariable ordinal logistic regression analyses, factors significantly associated with both moderate and severe malnutrition included age greater or equal to 65 years [(AOR = 4.32; 95% CI: (2.02, 9.28)], age 41–64 years [(AOR = 3.36; (1.58, 7.16)], male sex [(AOR = 1.46,95% CI:(1.085,1.953)], urban residence [(AOR = 0.49; 95% CI: (0.32, 0.76)], lack of formal education [(AOR = 5.37; 95% CI: (3.32, 8.69)], comorbidities at admission [(AOR = 1.50;95%CI:(1.04,2.16)], and inadequate dietary diversity [(AOR = 1.37;95% CI:1.01,1.86)]. Conclusion Malnutrition among hospitalized adult patients remains high and is strongly associated with age, sex, urban residence, educational status, comorbidities at admission, and dietary diversity. Therefore, hospital-based nutritional interventions should adopt a multidisciplinary approach, including early screening and identification, proper management of comorbidities, dietary counseling, and the development of comprehensive care plans and guidelines to improve clinical outcomes.